Анализа укорељености ЛПР-5, СОСТ и МХР са лошим прогнозама код пацијената са дијабетесом типа 2 компликованим остеопорозом: LPR-5, SOST i MHR za prelome kod osteoporoze uz dijabetes tipa 2 - Li, Xiang; Sun, Shiwei; Zhang, Tianlong; Li, Bohao; Zhang, Jiarui; Zhao, Yu; Xie, Yi; Yang, Siqi; Wang, Minghai (Journal of Medical Biochemistry, 2025)
Objective To evaluate the predictive value of the monocyte/high-density lipoprotein cholesterol ratio (MHR), low-density lipoprotein-associated protein (LRP)-5 and sclerosing protein (SOST) for fractures in patients with osteoporosis due to type 2 diabetes. Methods For the osteoporosis group, 218 individuals who received a type 2 diabetes diagnosis at this facility between January 2023 and December 2024 were chosen. Moreover, 90 patients with normal bone mass and 130 patients with decreased bone mass due to type 2 diabetes who were diagnosed at this center over the same time period were chosen as the normal bone mass group and the decreased bone mass group. Changes in the MHR, LPR-5 and SOST in each group and their relationships with the severity of fractures were observed. Binary logistic regression was used to analyze the influencing factors of fractures in patients with osteoporosis. Receiver operating characteristic (ROC) curves were used to assess the prediction effectiveness of the MHR, LPR-5, and SOST for fractures iin individuals with type 2 diabetes-related osteoporosis. Results In the osteoporosis group, the MHR and LPR-5 were substantially higher (P<0.05) than those in the osteopenia group, and in the osteopenia group, they were significantly higher than those in the normal bone mass group. The MHR and LPR-5 in the fracture group were significantly greater (P<0.05) than in the nonfracture group, and they also significantly increased as the fracture’s severity rose (P<0.05). Compared to the groups with osteopenia and normal bone mass, the osteoporosis group’s serum SOST level was considerably lower (P<0.05), and that in the osteopenia group was significantly lower than that in the normal bone mass group (P<0.05). The serum SOST level in the fracture group was significantly lower than that in the nonfracture group (P<0.05). Multivariate analysis revealed that BMI, FBG, the MHR, the LPR-5 and the SOST were independent influencing factors for fractures in patients with type 2 diabetes (P<0.05). The MHR, LPR-5, and SOST were significantly more predictive of fractures in patients with osteoporosis and type 2 diabetes than were BMI and FBG (P<0.01). The combined detection of the MHR, LPR-5 and SOST had a sensitivity of 87.5% and a specificity of 83.6% for diagnosing fractures in patients with osteoporosis and type 2 diabetes. While there was no statistically significant difference in the AUC of the individual detections of each index (P>0.05), the area under the curve (AUC) was 0.909, which was significantly greater than the AUC of the individual detections of MHR (Z=3.182, P<0.01), LPR-5 (Z=3.154, P<0.01), and SOST (Z=3.684, P<0.01). Conclusion The MHR, LPR-5, and SOST are independent determinants of fractures and contribute to the onset and progression of osteoporosis in people with type 2 diabetes. The combined detection of the above three indicators has high predictive value for fractures in patients with osteoporosis and type 2 diabetes.